1982
DOI: 10.1126/science.215.4531.421
|View full text |Cite
|
Sign up to set email alerts
|

Helpers: Effects of Experimental Removal on Reproductive Success

Abstract: Experimental removal of helpers from a communal bird population decreased the reproductive success of the reduced units. By controlling for variables that are potentially correlated with both reproductive success and unit size, this experiment establishes that helpers-contribute significantly to their indirect fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 16 publications
3
93
0
Order By: Relevance
“…Thus, in the case of helpers at the nest, it is possible to identify a set of territories with equivalent numbers of helpers present and then experimentally remove helpers from some nests, selected at random. Such experimental studies have confirmed the hypothesis that, at least in some species, the presence of helpers at the nest does increase the number of young fledged (Brown et al 1982).…”
Section: Experimental Approachsupporting
confidence: 65%
“…Thus, in the case of helpers at the nest, it is possible to identify a set of territories with equivalent numbers of helpers present and then experimentally remove helpers from some nests, selected at random. Such experimental studies have confirmed the hypothesis that, at least in some species, the presence of helpers at the nest does increase the number of young fledged (Brown et al 1982).…”
Section: Experimental Approachsupporting
confidence: 65%
“…For example, apparent helper effects on productivity can be non-causal [10,16]; so our predictions might not reflect true helper benefits from helping in groups of varying sizes. Group size manipulations [38] do not resolve this problem because only reductions are possible and they necessarily alter grouping benefits and disrupt social dynamics, making it difficult to verify that reductions in provisioning rates are caused by reductions in helper numbers [11]. Therefore, we used brood size manipulations which can circumvent the above problems [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Another option is to remove group members and compare the outcome (e.g. Brown et al 1982;Solomon 1991;Powell & Fried 1992), but here one should be cautious about interpreting the results of such experiments because they change group size as well as helper number (Cockburn 1998;Russell et al 2008).…”
Section: Maternal Effects As Confounds Of Fitness Estimatesmentioning
confidence: 99%